A AMARIV e suas aproximações e distanciamentos das características burocráticas e alternativas : uma análise crítica - Bernardes, Nayara Rodrigues (2017)
The present work has proposed to understand the approximations and distances of the management of the Association of Recyclable Materials Collectors of the Island of Vitória (AMARIV) in relation to bureaucratic organizational formats and those with altern